Pembelajaran Tatap Muka Sebagai Faktor Keputusan Orang Tua Memilih Pesantren di Masa Pandemi - Rasyidin, Rasyidin; Harahap, Radinal Mukhtar; Harahap, Arridha (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
This study examines how much face-to-face learning (PTM) factors influence parents' decisions in choosing Islamic boarding schools as educational institutions for their children during the pandemic (TA.2021-2022). Based on the literature review, there are five factors that influence parents' decisions in choosing pesantren as their child's educational institution, namely ideological, educational, structuralist, economic and pragmatic, or six factors for the case of schools in general, namely social status and income level, curriculum, facilities infrastructure, school achievement, location and educational environment, and teacher quality. This study found other factors that emerged due to the Joint Decree of the Minister of Education and Culture, the Minister of Religion, the Minister of Health and the Minister of Home Affairs of the Republic of Indonesia concerning Guidelines for the Implementation of Learning in the 2020/2021 Academic Year and the 2020/2021 Academic Year during the Covid-19 Pandemic Period. Islamic boarding schools allowed to carry out face-to-face learning with detailed provisions. According to data analysis conducted through tabulation, reduction and conclusion drawing, it was found that the PTM factor was quite influential for parents so it was recommended for Islamic boarding schools to detail the narrative of their face-to-face learning process next year to maintain public trust -which could be for this year- based solely on the compulsion of conditions. This research was conducted by conducting in-depth interviews with several parents while still considering reviewing the document data for accepting new students at the Ar-Raudlatul Hasanah Islamic Boarding School, Medan.